2018
DOI: 10.1155/2018/6130487
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A45HTTLPR Polymorphism Affects Insulin Secretion in Patients with Polycystic Ovary Syndrome

Abstract: Purpose To investigate in a pilot study of genetic polymorphisms in serotonin system influencing basal- and glucose-stimulated insulin secretion in women with polycystic ovary syndrome (PCOS). Methods A cross-sectional study included 65 female patients with PCOS followed up at the endocrine outpatient clinic of the University Medical Center Ljubljana and a control group of 94 young healthy female blood donors. Oral glucose tolerance test was performed only in PCOS patients and basal- and glucose-stimulated blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…SLC6A4 encodes an integral membrane protein, which act as the role to transport the neurotransmitter serotonin from synaptic spaces into presynaptic neurons. SLC6A4 5HTTLPR polymorphism was revealed to be related to insulin blood levels and insulin secretion during OGTT in patients with polycystic ovary syndrome (PCOS) [ 39 ]. Recent research has implied that BSN acted in concert to control presynaptic autophagy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…SLC6A4 encodes an integral membrane protein, which act as the role to transport the neurotransmitter serotonin from synaptic spaces into presynaptic neurons. SLC6A4 5HTTLPR polymorphism was revealed to be related to insulin blood levels and insulin secretion during OGTT in patients with polycystic ovary syndrome (PCOS) [ 39 ]. Recent research has implied that BSN acted in concert to control presynaptic autophagy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased Drd2 expression in the Evidence-Based Complementary and Alternative Medicine theca was related to an increased vascularization in the theca of PCOS follicles, and overproduction of VEGF may lead to ovarian hyperstimulation syndrome [36,38]. SLC6A4 5HTTLPR polymorphism was related to insulin secretion and insulin blood levels during OGTT in patients with PCOS [39]. CDK2 is a cell cycle regulator, and the PCOS condition is related to the increased nuclear abundance of CDK2 in the endometrial epithelial cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed the role of the SLC6A4 gene in insulin secretion in patients with polycystic ovary syndrome. Polymorphism in SERT alters insulin secretion in these individuals (27). The discovery of these genetic changes in diabetes reveals the functional role of genetic changes in the development of the disease.…”
Section: Association Of Slc6a4 Gene With Diabetesmentioning
confidence: 99%